Exploring and understanding adverse effect of Proton Pump Inhibitors - Hoque Majedul M. (Srpsko lekarsko drustvo, 2024)
Introduction: Over the past few decades, proton pump inhibitors (PPIs) have been used more often; nonetheless, there are concern regarding misuse and the severe adverse effects that have been described. Methods: This paper will present information from relevant professional/scientific sources including Scopus, EBSCO, PubMed regarding unwanted adverse events of PPIs. Topic: The causality of correlations between PPI usage and possible adverse effects is unknown. Increased risk of kidney, liver, and cardiovascular disease; dementia; gastrointestinal tract enteroendocrine tumors; susceptibility to respiratory and gastrointestinal infections; and reduced nutritional absorption are just a few of the long-term adverse effects of widespread use of PPI that have come to light. Thus, given growing concerns regarding PPI overuse in the general population, the purpose of this investigation is to review the relationship between PPI usage and the risk of major side consequences. Conclusion: Due to the numerous known side effects of PPIs on the system, further study is necessary, including changing the drug's molecular structure and creating a new medication from its parent. By administering these drugs effectively for the relevant diagnosis, reevaluating patients' symptoms on a regular basis to determine the least amount and duration of therapy, and closely monitoring any potential side effects, it is feasible to minimize expenditures with health risk and maximize beneficial outcomes.